(untitled) (Research, Society and Development, 2021)
The Brazilian agricultural market has grown and occupies more and more space in the world economy. Brazil is the second largest producer and consumer of beef, behind only the United States. The intrinsic factors of meat contribute to microbial proliferation and rapid deterioration, and there is a need to produce a natural alternative for food preservation, being accessible and at a low cost to the population. The objective of this work was to evaluate the conservation potential of Manihot esculenta gel added with copaiba essential oil (Copaifera officinalis) and beet extract (Beta vulgaris L.) in extending the shelf life of beef. The antimicrobial potential of copaiba oil was determined by disc diffusion, determination of the minimum inhibitory and bactericidal restrictions of the oil by microdilution, chemical composition, shelf life through color, pH and microbiota during the period of storage of controls and control. Among the results, the initial pH of the control sample was 5.25 ± 0.05 and the final 5.93 ± 0.03, the OCB sample 5.28 ± 0.01 at the end 5.37 ± 0.008 and the BET sample between 5 , 21 ± 0.08 to 5.39 ± 0.05. An initial microbiological analysis of the control sample of mesophiles at 20 minutes from 3.06 to 5.27 log UFC / g on the 7th day, the OCB sample started 3.26 to 5.14 log UFC / g and the BET sample, started from 3.39 to 4.73 log UFC / g. The results obtained arouse studies to explore new dosages in this matrix.